2000
DOI: 10.2741/zafonte
|View full text |Cite
|
Sign up to set email alerts
|

Cell-cycle dysregulation in breast cancer: breast cancer therapies targeting the cell cycle

Abstract: Breast cancer is the most commonly diagnosed cancer in American women. The underlying mechanisms that cause aberrant cell proliferation and tumor growth involve conserved pathways, which include components of the cell cycle machinery. Proto-oncogenes, growth factors, and steroids have been implicated in the pathogenesis of breast cancer. Surgery, local irradiation, and chemotherapy have been the mainstay of treatment for early and advanced stage disease. Potential targets for selective breast cancer therapy ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 215 publications
1
37
0
3
Order By: Relevance
“…G1/S progression is tightly regulated by the pro-proliferative Cyclin D1 and CDK4 (17). Overexpression of Cyclin D1 and CDK4 is commonly detected in various types of cancer (18)(19)(20)(21). Consistent with the inhibitory effect of PZH on G1/S transition, our data indicated that PZH treatment suppressed the mRNA and protein expression of Cyclin D1 and CDK4 in Caco-2 cells.…”
Section: Pzh Regulates the Expression Of Cyclin D1 And Cdk4 Insupporting
confidence: 74%
See 1 more Smart Citation
“…G1/S progression is tightly regulated by the pro-proliferative Cyclin D1 and CDK4 (17). Overexpression of Cyclin D1 and CDK4 is commonly detected in various types of cancer (18)(19)(20)(21). Consistent with the inhibitory effect of PZH on G1/S transition, our data indicated that PZH treatment suppressed the mRNA and protein expression of Cyclin D1 and CDK4 in Caco-2 cells.…”
Section: Pzh Regulates the Expression Of Cyclin D1 And Cdk4 Insupporting
confidence: 74%
“…G1/S progression is strongly regulated by Cyclin D1, which exerts its function by forming an active complex with its major catalytic partners, such as CDK4 (17). An unchecked or hyperactivated Cyclin D1/CDK4 complex often leads to uncontrolled cell division and malignancy (18)(19)(20)(21). Therefore, inhibiting excessive proliferation of tumor cells by blocking Cyclin D1/CDK4-mediated G1/S progression is one of the key approaches for the development of anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that the CCND1 GA or AA genotype may augment the various influences of oestrogen in decreasing the risk of colorectal cancer and adenoma as well as increasing the risk of breast cancer. In previous studies, CCND1 can bind directly to the oestrogen receptor, transactivate oestrogen response elements (Zhou et al, 2001), and regulate oestrogen-dependent enhancer activity (Zafonte et al, 2000).…”
Section: Discussionmentioning
confidence: 89%
“…A potential BRCA1-responsive element was localized to position À615 to À511 of the p27 KIP1 promoter. p27 KIP1 is thought to function as a tumor suppressor and to be a target for cell cycle dysregulation during mammary carcinogenesis (Zafonte et al, 2000). Thus, low p27 KIP1 expression in breast cancer specimens is correlated with histological aggressiveness and poor prognosis (Chiarle et al, 2001); and mice that are genetically heterozygous for p27 KIP1 show an increased susceptibility to tumorgenesis (Fero et al, 1998).…”
Section: Regulation Of Transcriptionmentioning
confidence: 99%